Reverse contrast enhancement in digital radiography in detection of vertical root fracture (in vitro) - Sandra Mehralizadeh; Peyman Mehrvarzfar; Sima Taghizadeh; Maryam Edalat; Mahashad Mohebi (Tehran University of Medical Sciences, 2015)
Background and Aims: Diagnosis of vertical root fractures often poses a clinical dilemma. Diagnosis of VRF in intraoral radiographs, except in cases where the beam is perpendicular to the direction of fracture is difficult. Misdiagnosis often leads to wrong decisions about the design of teeth future treatment plan. The aim of this study was to determine the diagnostic accuracy of reverse contrast enhancement options in digital radiography, and to compare it with the original images to find a suitable method to detect vertical root fracture.   Materials and Methods: In this experimental study, digital radiography with phosphor plate detector was taken from 40 extracted single root teeth. From each intact and fractured tooth, the original and reverse contrast images captured and stored. Two expert observers viewed the images twice with an interval of two weeks. Diagnostic criteria (Accuracy, PPV, NPV, Specificity and Sensitivity) in form of absolute and complete for each observer and each images was calculated. Inter and intra observer reliability was obtained using Mc-Nemar test.   Results: No significant differences in inter-observer reliability between the initial appearance and reverse contrast was observed (P>0.05), but in view of the intra-observer reliability in two cases, the difference was significant (P<0.05). No significant difference in the accuracy, sensitivity, specificity and PPV was observe between the two used images (P>0.05), whereas significant difference between the two images was found in NPV index (P<0.05).   Conclusion: The use of reverse contrast enhancement option for detection of vertical root fracture did not show significant difference from initial view.